Synthesis and Optimization of a Bifunctional Hyaluronan‐Based Camptothecin Prodrug. Issue 4 (9th January 2014) - Xu, Zaiyang; Zheng, Wenyi; Yin, Zongning
<x xml:space="preserve">Abstract</x> Aiming to overcome the low solubility and poor targeting ability of camptothecin (CPT), two hyaluronan (HA)‐based polymeric prodrugs with different molecular weights (MW) were synthesized and characterized. The structure of HA–CPT was thoroughly verified by ultraviolet (UV), infrared (IR), 1H nuclear magnetic resonance (1H NMR), differential scanning calorimetry (DSC), and high performance liquid chromatography (HPLC). The conjugation of CPT to HA successfully improved the solubility of CPT from 2.08 to 420–620 µg/mL and enhanced tumor targeting, as shown by the in vitro uptake and cytotoxicity results. Moreover, it was found that the high MW conjugate exhibited higher drug loading, higher stability but lower solubility compared with the low MW conjugate. Both HA–CPT conjugates exhibited similar uptake efficiency and antitumor activity. The results demonstrated that HA could act as an effective solubilization carrier and targeting molecule in a HA‐based CPT prodrug.